Analytical elements of mechanics. - Kane, Thomas R. (Academic Press, 1961)
Analytical Elements of Mechanics, Volume 2: Dynamics focuses on the processes, methodologies, approaches, and technologies involved in classical mechanics. The book first offers information on the differentiation of vectors, including vector functions of a scalar variable; derivatives of sums and products; vector tangents of a space curve; vector binormals of a space curve; and Taylor's theorem for vector functions. The manuscript then ponders on kinematics, as well as angular velocity and acceleration, absolute and relative velocity and acceleration, and rates of change of orientation of a r.